2019
DOI: 10.3389/fnagi.2019.00193
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Reductions in Tactile and Motor Inhibitory Function Start Early but Are Independent

Abstract: Aging is associated with declines in motor and somatosensory function. Some of these motor declines have been linked to age-related reductions in inhibitory function. Here we examined whether tactile surround inhibition also changes with age and whether these changes are associated with those in the motor domain. We tested a group of 56 participants spanning a wide age range (18–76 years old), allowing us to examine when age differences emerge across the lifespan. Participants performed tactile and motor tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
5
13
1
Order By: Relevance
“…Although we observed a relationship between age differences in motor and somatosensory neural representations in the current study, we did not observe a relationship between motor and tactile behavioral measures, either in the present study or in our previous study (Ruitenberg et al 2019). One reason for this discrepancy between the neural and behavioral relationships may be that tactile stimulation during fMRI scanning was passive, whereas the (outside of scanner) tactile behavioral tasks were active.…”
Section: Age Differences In Somatosensory System Are Related To Age Differences In Motor Systemcontrasting
confidence: 98%
See 4 more Smart Citations
“…Although we observed a relationship between age differences in motor and somatosensory neural representations in the current study, we did not observe a relationship between motor and tactile behavioral measures, either in the present study or in our previous study (Ruitenberg et al 2019). One reason for this discrepancy between the neural and behavioral relationships may be that tactile stimulation during fMRI scanning was passive, whereas the (outside of scanner) tactile behavioral tasks were active.…”
Section: Age Differences In Somatosensory System Are Related To Age Differences In Motor Systemcontrasting
confidence: 98%
“…The results from the motor tapping task have been reported previously in our previous study (Ruitenberg et al 2019). In short, we observed that age significantly predicted the intrahemispheric between-finger lag, such that increasing age was associated with an increased duration of the between-finger lag (B = 2.22, t = 4.14, P < 0.001).…”
Section: Motor Tapping Performancesupporting
confidence: 89%
See 3 more Smart Citations